A critical review of selected appropriate traditional evaporative cooling as postharvest technologies in Eastern Africa - Obura, J. M.; Banadda, N.; Wanyama, J.; Kiggundu, N. (Agricultural Engineering International, 2015)
The issue of postharvest losses (PHL) is of high importance in the efforts to combat hunger, raise income and improve food security in the world’s poorest countries. PHL of horticultural products in developing countries sometimes may reach up to 45%. PHL have an impact on food security for poor people, food quality and safety, economic development and the environment. The exact causes of PHL vary throughout the world and are very much dependent on the specific conditions and local situation in a given country. Irrespective of the level of economic development and maturity of systems in a country, PHL should be kept to a minimum. The failure to harness the physical and chemical characteristics of horticultural products using technologies has been very costly to farmers, processors and marketers in many parts of the world. A number of researchers and undocumented indigenous African Knowledge custodians in rural areas have innovated and constructed different technologies using locally available materials for the purpose of extending the shelf life of horticultural produce like vegetables. This review article seeks to critically examine some of the selected agricultural technologies and equipment used in African rural settings with view of assessing why they fail.
Keywords: Perishables; Technologies; Technology use; Shelf life